Identification of Azole Resistance Markers in Clinical Isolates of Candida tropicalis Using cDNA‐AFLP Method. Issue 3 (14th April 2015) - Kanani, Ali; Zaini, Farideh; Kordbacheh, Parivash; Falahati, Mehraban; Rezaie, Sassan; Daie, Roshanak; Farahyar, Shirin; Safara, Mahin; Fateh, Roohollah; Faghihloo, Ebrahim; Fattahi, Azam; Heidari, Mansour
Abstract : Background: Global reports have highlighted the increasing prevalence of Candida tropicalis infections as well as organism ' s drug resistance. This study aimed at identifying azole resistance markers in clinical isolates of C. tropicalis, which will be a great resource for developing new drugs. Methods: Two susceptible and resistant isolates of C. tropicalis were recovered from an epidemiological investigation of candidiasis in immunocompromised patients. C. tropicalis ATCC 750 was used as reference strain. Antifungal susceptibility to fluconazole and itraconazole was determined using Clinical and Laboratory Standards Institute (CLSI) method. Complementary DNA‐amplified fragment length polymorphism (cDNA‐AFLP) technology and real‐time reverse‐transcriptase (RT) PCR were used for identification of potential genes involved in azole resistance of C. tropicalis clinical isolates. Results: Five genes encoding the following enzymes were identified as superoxide dismutase ( SOD ) implicated in antioxidant defense, ornithine aminotransferase ( OAT ), acetyl ornithine aminotransferase ( ACOAT ), adenosylmethionine‐8‐amino‐7‐oxononanoate aminotransferase ( DAPA AT ), and 4‐aminobutyrate aminotransferase ( ABAT )—belonging to pyridoxal phosphate (PLP) dependent enzymes and acting in an important physiological role in many fungal‐cell cycles. Real‐time RT‐PCR confirmed mRNA level of the aforementioned genes. Conclusion: Our findings showed that factors such as PLP‐dependent enzymes and SOD might be implicated in drug resistance in C. tropicalis clinical isolate. Therefore, further studies are required to explore the accurate biological functions of the mentioned genes that would be helpful for effective drug development.